REDES NEURAIS ARTIFICIAIS PARA ESTIMAÇÃO DE VELOCIDADE EM MÁQUINAS DE INDUÇÃO - Mouzinho, Lucilene Ferreira (2003)
This work presents an artificial neural network model to estimate or indirectly measure the speed of three-phase induction machines for control purpose. A comparative analysis of the neural estimator is performed with the following types of speed estimators: rotor flux, electromotive force and model reference adaptive. The algorithms of the estimators are assembled and connected to the dq0 model of the induction machine. Computational simulation results, obtained from machine-estimators model, are used to carry out a comparative analysis of the speed estimators performance. This work also presents a survey on neural network applications in induction machines, covering the following issues: control, failure, supervision, diagnosis, identification and estimation.